You are on page 1of 5

# A Generalization of Riemann Sums

Omran Kouba

Abstract
We generalize the property that Riemann sums of a continuous function
corresponding to equidistant subdivisions of an interval converge to the integral
of that function. We then give some applications of this generalization.

## Problem U131 in  reads:

Prove that
n
X arctan k n (k) 3 log 2
lim = , (1)
n n+k k 4
k=1
where denotes Eulers totient function. In this note we prove the following theo-
rem, that will, in particular, answer this question.

Theorem 1. Let be a positive real number and let (an )n1 be a sequence of positive
real numbers such that
n
1 X
lim ak = L.
n n
k=1
For every continuous function f on the interval [0, 1],
n   Z 1
1 X k
lim f ak = L x1 f (x) dx.
n n n 0
k=1

n
1 X 1
lim k =
n n+1 +1
k=1

## fact 2 if (n )n1 is a real sequence that converges to 0, and > 0 then

n
1 X
lim k k = 0.
n n+1
k=1

Indeed, fact 1 is just the statement that the Riemann sums of the function
x 7
R 1x corresponding to an equidistant subdivision of the interval [0, 1] converges
to 0 x dx.

## Mathematical Reflections 1 (2010) 1

The proof of fact 2 is a Cesaro argument. Since (n )n1 converges to 0 it
must be bounded, and if we define n = supkn |k |, then limn n = 0. But, for
1 < m < n, we have

1 X n m n

1 X 1 X
k k +1 k |k | + +1 k |k |

+1
n n n
k=1 k=1 k=m+1
m+1
1 + m .
n+1
Let  be an arbitrary positive number. There is an m > 0 such that m < /2.
Then we can find n > m such that for every n > n we have m+1
 1 /n+1 < /2.
Thus
1 X n

n > n = +1 k k < .

n
k=1
This ends the proof of fact 2.

Now, we come to the proof of our Theorem. We start by proving the following
property by induction on p :
n
1 X
lim k p ak = L. (2)
n n+p +p
k=1

The base property (p = 0) is just the hypothesis. Let us assume that this is true
for a given p and let
n
1 X p L
n = +p k ak ,
n +p
k=1
(with the convention 0 = 0,) so that limn n = 0. Clearly,
L
k p ak = k +p k (k 1)+p k1 + k +p (k 1)+p ,

+p
hence
L
k p+1 ak = k +p+1 k k(k 1)+p k1 + k +p+1 k(k 1)+p ,

+p
L
= k +p+1 k (k 1)+p+1 k1 + k +p+1 (k 1)+p+1

+p
L
(k 1)+p k1 (k 1)+p
+p
It follows that
n n1 n1
!
1 X
p+1 1 X
+p L 1 X
+p
k ak = n k k + 1 k .
n+p+1 n+p+1 +p n+p+1
k=1 k=1 k=1

## Mathematical Reflections 1 (2010) 2

Using fact 1 and fact 2 we conclude that
n  
1 X
p+1 L 1 L
lim k ak = 1 = .
n n+p+1 +p +p+1 +p+1
k=1

## For a continuous function f on the interval [0, 1] we define

n   Z 1
1 X k
In (f ) = f ak , and J(f ) = L x1 f (x) dx.
n n 0
k=1

Now, if X p denotes the function t 7 tp , then (2) is equivalent to the fact that
limn In (X p ) = J(X p ), for every nonnegative integer p. Using linearity, we con-
clude that limn In (P ) = J(P ) for every polynomial function P .

## On the other hand, if M = supn1 n1 nk=1 ak , then L M and we observe

P
that for every continuous functions f and g on [0, 1] and all positive integers n,

[0,1] [0,1]

## Consider a continuous function f on [0, 1]. Let  be an arbitrary positive num-

ber. Using Weierstrass Theorem there is a polynomial P such that ||f P || =

supx[0,1] |f (x) P (x)| < 3M . Moreover, since limn In (P ) = J(P ), there exists
an n such that |In (P ) J(P )| < 3 for every n > n . Therefore, for n > n , we
have

|In (f ) J(f )| |In (f ) In (P )| + |In (P ) J(P )| + |J(P ) J(f )| < .

## This ends the proof of Theorem 1.

Applications.

It is known that Eulers totient function has very erratic behaviour, but on
the mean we have the following beautiful result, see [2, 18.5],
n
1 X 3
lim (k) = 2 . (3)
n n2
k=1

Using Theorem 1 we conclude that, for every continuous function f on [0, 1],
n   Z 1
1 X k 6
lim 2 f (k) = 2 xf (x) dx. (4)
n n n 0
k=1

## Mathematical Reflections 1 (2010) 3

arctan x
Choosing f (x) = x(1+x) we conclude that

n Z 1
X arctan(k/n) 6 arctan x
lim (k) = dx. (5)
n k(n + k) 2 0 1+x
k=1
R1
Thus we only need to evaluate the integral I = 0 arctan x
1+x dx. The easy way
1t
to do this is to make the change of variables x 1+t to obtain
1   1
1t
Z Z
dt  dt
I= arctan = arctan t
0 1+t 1+t 0 4 1+t
Z 1
dt
= I
4 0 1+t

Hence, I = 8 log 2. Replacing back in (5) we obtain (1).

Similarly, if (n) denotes the sum of divisors of n, then (see [2, 18.3]),
n
1 X 2
lim 2 (k) = .
n n 12
k=1

Using Theorem 1 we conclude that, for every continuous function f on [0, 1],
n
2 1
  Z
1 X k
lim f (k) = xf (x) dx.
n n2 n 6 0
k=1

1
Choosing for instance f (x) = 1+ax2
we conclude that
n
X (k) 2
lim = log(1 + a).
n n2 + ak 2 12a
k=1

Starting from
n
1 X (k) 6
lim = 2,
n n k
k=1

which can be proved in the same way as (3), we conclude that, for every 0,
n
1 X 6
lim k 1 (k) = (6)
n n+1 2 (1 + )
k=1

## Mathematical Reflections 1 (2010) 4

Also,
n Z 1
1 X 6
lim k 1 log(k/n)(k) = x log(x) dx
n n+1 2 0
k=1
6
= .
2 ( + 1)2

## Hence, using (6), for 0 we obtain:

n 
1 X
1 6 (1 + ) log n 1
k log k (k) = + o(1).
n+1 2 (1 + )2
k=1

References
 C. Lupu, Problem U131, Mathematical Reflections. (4) (2009).

##  G. H. Hardy and E. M.Wright, An Introduction to the Theory of Numbers (5th

ed.), Oxford University Press. (1980).

Omran Kouba
Department of Mathematics
Higher Institute for Applied Sciences and Technology
P.O. Box 31983, Damascus, Syria.
omran kouba@hiast.edu.sy